Well done, the naughtiest girl! - Digby, Anne; Blyton, Enid (Hodder Children's London, 1999)
Elizabeth is desperate to play the piano in the end of school concert. But when Arabella is chosen over her, she realises that she might well also fail all her exams. Racing to get her revision done, she finds a quiet spot in an old oak tree which is marked as one to be chopped down. Can she save the tree and manage to pass all her exams?